PERBEDAAN PERLUASAN DAERAH TUTUPAN PADA WILAYAH PERMUKIMAN DI KOTAMADYA DEPOK - Saraswati, Ratna (UI Scholars Hub, 2002)
The Depok Land Use Planning predicts that in 2010, urban land use will be 73 percent, while 63 percent is for settlement. Depok is allocated for catchment area, so the expansion of paving area should be monitor. In this study, there were four types of settlement lower and middle type in perumnas and in middle type (perumnas kecil dan besar serta perumahan sederhana kecil dan besar). Average of paved area in the perumnas kecil was 66 m², in perumnas besar was 89.5 m². In perumahan sederhana kecil was 54.4 m² and in perumahan sederhana besar was 121.3 m². Land square meter and length of stay were the variables that infl uence the expansion of paved area. They did that because they have more space to expand their house, and now, there was no open space left